The impact of improved access to after-hours primary care on emergency department and primary care utilization: A systematic review. Issue 8 (August 2020) - Hong, Michael; Thind, Amardeep; Zaric, Gregory S.; Sarma, Sisira
Highlights: Access to after-hours primary care physicians increases primary care utilization. Better access to after-hours primary care may reduce non-urgent ED utilization. Cost-savings of initiatives improving after-hours primary care access is unclear. Controlled pre-post design or quasi-experimental studies are needed in this area. Abstract: Access to after-hours primary care is problematic in many developed countries, leading patients to instead visit the emergency department for non-urgent conditions. However, emergency department utilization for conditions treatable in primary care settings may contribute to emergency department overcrowding and increased health system costs. This systematic review examines the impact of various initiatives by developed countries to improve access to after-hours primary care on emergency department and primary care utilization. We performed a systematic review on the impact of improved access to after-hours primary and searched CINAHL, EMBASE, MEDLINE, and Scopus. We identified 20 studies that examined the impact of improved access to after-hours primary care on ED utilization and 6 studies that examined the impact on primary care utilization. Improved access to after-hours primary care was associated with increased primary care utilization, but had a mixed effect on emergency department utilization, with limited evidence of a reduction in non-urgent and semi-urgent emergency department visits. Although our review suggests that improved access to after-hours primary care may limit emergency department utilization by shifting patient care from the emergency department back to primary care, rigorous research in a given institutional context is required before introducing any initiative to improve access to after-hours primary care.